THE INFLUENCE OF TYPE OF UNIVERSITY ON STUDENTS' INTERNET INSIGHT AS AN ACADEMIC RESOURCE TOOL IN KENYAN UNIVERSITIES - Obulinji, Musamia; Korir, Ruto; Kiaritha , Njeri; Mulambula, Shikuku (American Journal of Education and Practice, 2021)
Purpose: The aim of the paper is to find out the impact of type of university on the insight students have about the internet as a learning tool in universities based in Kenya. Methodology: Quantitative research approach was undertaken. An ex post facto research survey design was adopted. The researcher used a representative sample of 435 (Moi University) and 175 (Daystar University)adding up to 610 Third year student teachers of the academic year 2015/2016 drawn from School of Education in the two universities. Stratified sampling was used to categorize students by gender from each stratum; participants were chosen randomly. Questionnaires were used as instruments of data collection. Content validity was established by use of expert judgment in the school of education. Test re-test method was used to establish the reliability of instruments of data collection. Descriptive and inferential statistics were applied for data analysis. The inferential statistics used was mean, data frequencies and percentages. Several tests were used to test the hypothesis, that is, Post hoc, Chi square and Analysis of variance. Results: The study findings indicated no significant relationship between university type and internet knowledge, perceived internet ease of use and internet self-efficacy. Unique contribution to practice, theory, and strategy: The outcome of the study is useful in designing educational programs in Kenyan institutions of higher learning and also, creates an avenue to link the knowledge gap in digital divide research field, to be used later for technology acceptance studies.